Tephritid fruit fly species composition, seasonality, and fruit infestations in two central African agro-ecological zones - Nanga, S.N.; Hanna, R.; Fotso Kuate, A.; Fiaboe, K.; Nchoutnji, I.; Ndjab, M.R.; Gnanvossou, D.; Mohamed, S.A.; Ekesi, S.; Djieto-Lordon, C. (MDPI, 2022)
Bactrocera dorsalis and several Africa-native Ceratitis species are serious constraints to fruit production in sub-Saharan Africa. A long-term trapping and fruit collection study was conducted (2011–2016) in two contrasting agro-ecological zones (AEZs) of Cameroon to determine fruit fly species composition, seasonality, attraction to various lures and baits, and fruit infestation levels. Ten tephritid species from genera Bactrocera, Ceratitis, Dacus, and Perilampsis were captured in traps. Bactrocera dorsalis was the most dominant of the trapped species and persisted throughout the year, with peak populations in May–June. Ceratitis spp. were less abundant than B. dorsalis, with Ceratitis anonae dominating in the western highland zone and Ceratitis cosyra in the humid forest zone. Methyl eugenol and terpinyl acetate captured more B. dorsalis and Ceratitis spp., respectively than Torula yeast. The latter was the most effective food bait on all tephritid species compared with Bio- Lure and Mazoferm. Bactrocera dorsalis was the dominant species emerging from incubated fruits, particularly mango, guava, and wild mango. Four plant species—I. wombolu, Dacryodes edulis, Voacanga Africana and Trichoscypha abut—were new host records for B. dorsalis. This study is the first long-duration and comprehensive assessment of frugivorous tephritid species composition, fruit infestations, and seasonality in Central Africa.